Observations on housing planning and development in Madinah during the Prophet’s time - Spahic, Omer (The Islamic Cultural Centre and London Central Mosque, London, 2014)
This paper discusses several social and religious aspects of the housing planning and development in Madinah during the Prophet Muhammad’s era. The paper focuses on the housing area that surrounded the Prophet’s mosque which, in turn, functioned as a community development center. The paper concludes that housing played a significant role in developing and managing the first Muslim community in Madinah on account of the house phenomenon in Islam denoting a physical locus of the family institution without which the fulfillment of the divine purpose on earth is virtually impossible. By means of housing, strengthening fraternity among the Muslims was intended to be achieved. Through it, the urbanization and development of the city-state were meant to be further intensified and sustained. Some core Islamic principles underscoring the philosophies of housing and man, and what relationship ought to exist between them, have thus also been put into practice. By exploring those topics, the strength and integrity of the fundamentals of the first Muslim community clearly come into sight, as does the visionary disposition of the Prophet (pbuh) to development, leadership and management. The nature of the paper, along with its content, methodology and conclusions, is conceptual and philosophical, rather than empirical.